The nexus of banks' competition, ownership structure, and economic growth on credit risk and financial stability - Md Abdul Halim; Syed Moudud-Ul-Huq; Farid Ahammad Sobhani; Ziaul Karim; Zinnatun Nesa (Economies, 2023)
The main object of this research is to find out the nexus of banks' competition, ownership structure, and economic growth on credit risk and financial stability. In addition, it examines the level of financial stability, economic growth, and ownership structure in the Middle East and North African (MENA) economies. The generalized method of moments (GMM) method was used to examine this study. The study used an unbalanced panel dataset from 2011 to 2021 in MENA countries. This research demonstrates a negative relationship between economic growth, credit risk, and financial stability in MENA economies; nevertheless, it proves an insignificant effect among them. It also shows that the lower the level of bank competition, the lower the level of bank risk taking, and the better the level of financial stability. It further found that market competition and bank ownership structure had a homogenous effect on financial stability when looking at the impact of competition and bank ownership structure. In the long-term sense, the square term of competition is highly favorable with financial stability models ((Lerner square Islamic banks), (Lerner square commercial banks), (Lerner square specialized government institutions)). However, financial stability improves with time, as seen by the competition square term bank ownership structure (a square measure of competition) with the Lerner index (LI) and the Herfindahl-Hirschman index total assets (HHIA). This finding of the square measure of competition is supported by competition stability theory. However, this study also proved that Islamic and commercial banks are less vulnerable to credit risk than specialized government institutions (SGI). This study scrutinized how MENA economies can remain stable through banking competition. This study builds a new brand of literature review. As a result, this research gives MENA policymakers better ideas for making policies that help the banking environment.
Keywords: 330; bank competition; credit risk; economic growth; financial stability; ownership structure; quadratic effect of bank competition